METODE PENURUNAN NILAI TAHANAN PEMBUMIAN DENGAN MENGGUNAKAN SEMEN KONDUKTIF - Miduk Purba; Angelia Purba (Universitas Quality, 2019)
Reliability and the existence of a reliable and sustainable electric power are very basic needs in the life of today's era. There are a number of things that can affect the reliability of electric power, one of which is protection that is standard and reliable. Grounding on the network must be within the specified standard limits. There are several ways that can be used to improve the value of grounding resistance, including by parallelizing the grounding electrode with other electrodes as far as two times the length of the electrode. In this way the value of the grounding resistance of half of the early grounding prisoners will be obtained. In this basic competency study using new breakthroughs on the method of decreasing the value of grounding resistance using conductive cement. Conductive cement made from charcoal mixed with cement, the value of earth resistance can be reduced without having to add new electrodes. This method can be applied in a number of cases such as limited land and also other obstacles to electrode installation such as the presence of gas pipes under the network. The use of conductive cement can also reduce the cost of decreasing the value of grounding resistance because it does not require a charge as large as the parallel electrode.